Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/btm2.10004
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic strategies for targeted nanoparticle delivery

Abstract: Nanoparticle‐based drug delivery and imaging platforms have become increasingly popular over the past several decades. Among different design parameters that can affect their performance, the incorporation of targeting functionality onto nanoparticle surfaces has been a widely studied subject. Targeted formulations have the ability to improve efficacy and function by positively modulating tissue localization. Many methods exist for creating targeted nanoformulations, including the use of custom biomolecules su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 210 publications
(368 reference statements)
0
99
0
Order By: Relevance
“…In the medical field, the impact of ‘bio-inspired design’ is realized in the areas of cellular engineering, tissue engineering, regenerative medicine, drug delivery and nanomedicine, and a variety of materials engineering to simulate extracellular matrix components. 1-3 A unique area of bio-inspired design that has generated significant academic and clinical research interest during past 30 years is that of bio-inspired nano-scale and micro-scale engineering of synthetic (or semi-synthetic) blood cells using a variety of biomaterials-based systems. The central driving force for this research is to develop technologies that can simulate the structure and/or property of blood cells as well as plasma, to allow utilization of these technologies as ‘blood substitute’ when donor-derived blood is either not readily available or poses significant contamination risks.…”
Section: A Introductionmentioning
confidence: 99%
“…In the medical field, the impact of ‘bio-inspired design’ is realized in the areas of cellular engineering, tissue engineering, regenerative medicine, drug delivery and nanomedicine, and a variety of materials engineering to simulate extracellular matrix components. 1-3 A unique area of bio-inspired design that has generated significant academic and clinical research interest during past 30 years is that of bio-inspired nano-scale and micro-scale engineering of synthetic (or semi-synthetic) blood cells using a variety of biomaterials-based systems. The central driving force for this research is to develop technologies that can simulate the structure and/or property of blood cells as well as plasma, to allow utilization of these technologies as ‘blood substitute’ when donor-derived blood is either not readily available or poses significant contamination risks.…”
Section: A Introductionmentioning
confidence: 99%
“…1,2 In the past decade, research within the fields of nanomedicine has demonstrated that nanodrug delivery systems could substantially improve drug bioavailability and local concentration by preventing premature degradation, controlled release, and enhanced permeability and retention effect. 3,4 However, rapid systemic elimination and unspecific and burst release are still major concerns that limit clinical potential of nanomedicine. To optimize nanodrug delivery system, design, and development of multivalent nanoparticles by surface conjugation of bioactive targeting moieties, stimuliresponsive monomers and anti-adsorptive copolymer blocks have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One way in which biomimetic design can enhance the utility of nanoparticle technology is by enabling targeted delivery through the use of natural ligands . A prominent example is arginylglycylaspartic acid (RGD), which is a binding peptide that can be found in fibronectin .…”
Section: Biomimetic Nanoparticle Technologymentioning
confidence: 99%